ANALISA PENGETAHUAN LANSIA DENGAN UPAYA PENCEGAHAN RHEUMATOID ARTHRITIS - Ricard Fredrik Marpaung (LPPM Universitas Abdurrab, 2023)
Rheumatoid Arthritis (RA) is an autoimmune and immune system disease that causes chronic inflammation of the joints. RA due to autoimmune reactions in synovial tissue involves the process of phagocytosis. The cause of RA is not clear until now, but heredity influences the emergence of this joint complaint. RA pain is generally often in the hands, elbow joints, ankles and knees. Pain and swelling in the joints can last continuously and the longer the symptoms of the complaint will be more severe (Chabib L, 2016). The high cases of RA in the elderly are influenced by knowledge and prevention efforts, where the elderly's knowledge of RA varies so that it affects behavior in maintaining and maintaining health in different ways. The purpose of the study was to analyze the knowledge of the elderly with efforts to prevent Rheumatoid Arthritis.The design of this study was descriptive with a cross-sectional research design. The population of this study was all elderly with RA amounting to 75 people. Data collection techniques use interview techniques in the form of questionnaires. The analysis used in this study was univariate and bivariate with Chi Square test. The results of the analysis There is a relationship between elderly knowledge and efforts to prevent rheumatoid arthritis in Sukaraja Village, Siantar Marihat District, Pematang Siantar City in 2023 where a p value of 0.000 â‰¤ 0.05 was obtained.